TEAM-BASED LEARNING TO IMPROVE STUDENTS’ UNDERSTANDING OF STATISTICS (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2018)
Cooperative approach has been proven to be one of successful learning strategies to improve learning. We investigated team-based learning (TBL) as a means to improve students’ understanding of statistics. Samples were 40 junior high schools students in West Java. Improvement after treatment was evaluated by an individual written test. Results suggested that students learning with TBL achieved better test results than control class. Description of team dynamics and its contribution to learning achievement is discussed.
Keywords: Team-Based Learning; Matematika; Pemahaman Matematik